The therapeutic potential of exosomal miR-22 for cervical cancer radiotherapy. Issue 12 (1st December 2020) - Konishi, Hiromi; Hayashi, Masami; Taniguchi, Kohei; Nakamura, Mayumi; Kuranaga, Yuki; Ito, Yuko; Kondo, Yoichi; Sasaki, Hiroshi; Terai, Yoshito; Akao, Yukihiro; Ohmichi, Masahide
ABSTRACT: Cervical cancer is the fourth-most prevalent malignancy in women. For advanced cervical cancer, radiotherapy is a major treatment. Micro RNAs (miRNAs) are small, noncoding RNAs that negatively regulate the target gene expression posttranscriptionally. miR-22 is frequently downregulated in various cancers including cervical cancer, and is associated with a poor prognosis in cervical cancer. Exosomes are small endosomally secreted vesicles that carry components such as proteins, messenger RNA (mRNA), DNA and miRNA. We investigated whether or not exosomes can efficiently deliver miR-22 to recipient cervical cancer cells and affect the gene expression in the cells, as well as assessed the role of exosomal miR-22 in radiosensitivity. Exosomes containing high levels of miR-22 were extracted by ultracentrifugation and then characterized by Western blotting, a nanoparticle tracking analysis and electron microscopy. The high presence of miR-22 in the exosome was confirmed by real-time polymerase chain reaction. After the administration of the collected exosomal miR-22 to SKG-II and C4-I cervical cancer cells, the level of miR-22 in the cells was significantly increased, indicating the absorption of the exosomal miR-22. When miR-22 encapsulated in exosomes was administered to the SKG-II cells, the level of c-Myc binding protein (MYCBP) and human telomerase reverse transcriptase (hTERT) was significantly decreased in correlation with increased radiosensitivity determined by a clonogenic assay. Taken together, these results suggest that the administration of exosomal miR-22 may be a novel drug delivery system for cervical cancer radiotherapy.